Metaphorical Perceptions of Home Patient Care Students Regarding the Definition of Elderly - Ertuğrul SARI; Esra BEKİRCAN; Neşe İŞCAN AYYILDIZ; Abdullah USTA (Yaşlı Sorunları Araştırma Derneği, 2023)
In this research, the perspectives of students enrolled in the home care nursing program towards the concept of aging were explored through metaphor analysis. A qualitative research method and case study design were employed in the study. The sample group of the study consisted of 70 students continuing their education in the home care nursing program of a state university in Turkey. The participating students were asked to complete the sentence "Aging is like... because..." The analysis of the collected data revealed 21 metaphors, leading to the emergence of three themes based on common characteristics of these metaphors. After content analysis, under the theme of dependency, metaphors such as compassion, dependency, loneliness, love, and empathy were identified. Under the theme of the source of light, metaphors likewise person, source of knowledge, and maturation were found. Finally, under the theme of the end of the road, metaphors including death, hopelessness, and regret were identified. In conclusion, the study indicated that the home care nursing students involved in the study had generally positive perceptions of aging; however, they also exhibited some negative perspectives such as helplessness and weakness.